Editing cassava sweet genes for resistance to Xanthomonas. Reporting period: Second Semester 2024 - Sanchez, Francisco J.; Zárate, Carlos A.; Szurek, Boris; Díaz, Paula A.; Chavarriaga, Paul (2024)
Cassava (Manihot esculenta Crantz) is considered the third most important crop globally. The mitigation of diseases like cassava bacterial blight (CBB), caused by the phytopathogenic bacterium Xanthomonas phaseoli pv. manihotis (Xpm) is key for the success of the crop. CBB leads to significant yield losses, ranging from 12% to 100%. One of the infection mechanisms employed by Xpm involves TALE-type proteins, which facilitate bacterial proliferation and the onset of disease symptoms. It has been demonstrated that virulence mechanisms activate certain gene families, including the SWEET gene family, which encodes sugar transporters (such as glucose and sucrose) that provide a carbon source for the bacteria to grow a cause infection. The aim of our research is to assess the resistance of cassava lines edited in the MeSweet 10a and 10e genes using CRISPR/Cas9 to confer resistance to CBB in the model variety 60444, susceptible to CBB. The goal is to evaluate the impact of editions in the promoter or coding regions for resistance to Xpm infection. Lines exhibiting the most promising mutations (INDELS) in targeted regions will be identified through molecular assays, whichthen will be established under in vitro and greenhouse conditions to be infected with Xpm strains and evaluatedisease resistance.